Analisis Peran Organisasi Kepemudaan Gerakan Pemuda Al Washliyah Provinsi Sumatera Utara Dalam Pencegahan Tindak Pidana Narkotika Di Kalangan Remaja Menurut Undang-Undang Nomor 40 Tahun 2009 Tentang Kepemudaan - Zulham Efendi Siregar; Nurhimmi Falahiyati; Sahbudi Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
Drug abuse has become a crisis that threatens various aspects of life, including physical, mental, and social health, and even the future of the younger generation. Globally, approximately 296 million people aged 15-64 will abuse drugs in 2023, representing approximately 5.8% of the adult population. In Indonesia, the prevalence of drug abuse in 2023 is projected to reach 1.73%, equivalent to 3.33 million people aged 15-64. Of this number, 312,000 are adolescents. This indicates that adolescents, as the nation's hope, are highly vulnerable to the distribution and influence of narcotics (BNN RI, 2025). The type of research used is empirical legal research. Empirical legal research is legal research that combines two approaches: a normative (legal) approach and a sociological (empirical) approach. The GPA plays a strategic role as an Islamic youth organization that not only fosters and develops the potential of its members but also serves as a moral bulwark in preventing drug crimes among adolescents through religious, educational, and social approaches. GPA's strategies and policies are comprehensive, encompassing internal development through enforcement of organizational rules, drug awareness campaigns, and the involvement of cadres in positive activities. GPA also synergizes its programs with government policies (particularly the P4GN) and collaborates with authorities and educational institutions. GPA's relationship with other youth organizations in North Sumatra is synergistic and collaborative, where cross-organizational cooperation further strengthens the collective movement against drugs and emphasizes the role of youth as the vanguard in safeguarding the nation's morality, health, and future.